Wehman's complete dancing master and call book: containing a full and complete description of all the modern dances, together with the figures of the German. - Harvey, J. H. (New York, H. J. Wehman, Publisher, 1889)
This is a typical example of a manual compiled from previously published materials and assembled by a publisher. The manual contains hints for balls and information on the performance of quadrilles and round dances. The popular parlor game known as the German or cotillon is given fifty-five figures.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals